Metode Tafsir Taysir Karimi Ar-Rahman - Khoirunnisah Daulay (IAIN Padangsidimpuan, 2022)
The background of the problem in this research is the santriyati at Pondok Pesantren An-Nur, Kec. Panyanggar, Padangsidimpuan City, learning interpretation with the methods applied by the curriculum of the Islamic boarding school, different from other pesantren but having the same goal, namely enriching the treasures of knowledge.The research entitled Tafsir Karimi Ar-Rahman Fi Tafsir Kalam al-Mannan Method at Pondok Pesantren an-Nur, Panyanggar Village, Padangsidimpuan City, has a problem formulation, namely how the Tafsir Karimi Ar-Rahman Fi Tafsir Kalam Al-Mannan method at Pondok Pesantren An- Nur Panyanggar, Padangsidimpuan City. The purpose of this study was to determine the method of Tafsir Taysir Karimi Ar-Rahman Fi Tafsir Kalam Al-Mannan at the An-Nur Panyanggar Islamic Boarding School, Padangsidimpuan City.This research is a field research that uses data collection techniques, namely, by observation, interviews, and documentation, but also takes several books related to the author's research. The method used in this research is descriptive.The results of this study indicate that the Tafsir Karimi Ar-Rahman Fi Tafsir Kalam Al-Mannan Tafsir Method at An-Nur Islamic Boarding School in Panyanggar Village, Padangsidimpuan City is to use the method of translating sentence-by-sentence then translating the verses followed by translating the whole. For the next meeting, there will be a repetition of past discussions using the method of reading, translating and repeating the mufridats, in order to remember the lessons that have passed.